Incorporation of catch crop residues does not increase phosphorus leaching: a soil column experiment in unsaturated conditions. (9th July 2014) - Vanden Nest, T.; Vandecasteele, B.; Ruysschaert, G.; Merckx, R.
Abstract Some studies suggest that incorporation of catch crop residues leads to increased availability of P to plants. However, little information is available on how this affects P leaching in soils with a high P load. We tested the effect of catch‐crop residue incorporation at the end of winter on the P leaching potential in a soil column experiment under unsaturated conditions using a typical sandy loam soil of NW Europe characterized by a high P load. We sampled the catch crops white mustard (Sinapis alba L.), Italian ryegrass (Lolium multiflorum L.), black oats (Avena strigosa L.) and a perennial ryegrass‐white clover mix (Lolium perenne L.‐Trifolium repens L.) from a field trial on catch crops and soil from the plots where they were grown. Plant biomass was incorporated taking account of the differences in conditions of the plant material at the end of winter and the biomass yield of each catch crop. Incorporation of catch‐crop residues decreased P leaching compared to the fallow treatment probably through immobilization of soil P during catch crop residue decomposition. The exception was black oats, where the leaching of P was the same as for fallow soil. We observed clear differences in C/N, C/P, water soluble and total P concentration, and biodegradability between the tested catch crops, which seemed to affect the P leaching. We conclude that the incorporation of catch crop residues under typical soil and weather conditions and agricultural practices of NW Europe does not increase the potential P leaching losses.